Application of Business Technology in Management: A Case Study of Using Technology Innovation to Improve Business Operational Efficiency and Effectiveness - Yusuf Iskandar; Mariam Mariam; Kurniawan Kurniawan (Westscience Press, 2023)
This research focuses on the application of business technology in management, specifically examining a case study of a conventional bank in Sukabumi. The objective of the study is to explore the use of technological innovation to increase the efficiency and effectiveness of business operations at the bank. The research methodology involves a comprehensive analysis of the technological innovations implemented, their impact on customer service and transaction processing, and the overall organizational performance. The findings reveal that the bank has successfully implemented online banking platforms, a mobile application, and advanced ATMs, resulting in improved customer service, streamlined transaction processing, and enhanced organizational performance. The study contributes to the existing literature by emphasizing the importance of technological innovation in the banking sector and providing recommendations for banks to optimize their technological investments.